Alignment between theory and practice in group development processes in the workplace: an experiential perspective. (2nd September 2019) - Gwandure, Calvin; Boshoff, Estelle
ABSTRACT: The study examined the alignment between group processes theory and practice from an experiential perspective in a South African work context. Training and development programmes focus on groups and teams to improve performance. The perspective of this study was that training and development programmes should develop teams within a life paradigm. Participants were 13 university graduates who held various positions in organisations. All participants were recruited from Johannesburg, were female and ages ranged from 24 to 31 years. A questionnaire developed for this study based on Wheelan`s integrative model of group development was used to collect information from participants. The snowballing method was used to access participants. Thematic content analysis was used to analyse data. The results revealed that theory was aligned to group training experience in organisations. Future studies could assess team-building initiatives and effectiveness at each stage of group development.